2020
DOI: 10.1103/physrevd.101.103025
|View full text |Cite
|
Sign up to set email alerts
|

Tidal deformations of neutron stars with elastic crusts

Abstract: With the first detections of binary neutron star mergers by gravitational-wave detectors, it proves timely to consider how the internal structure of neutron stars affects the way in which they can be asymmetrically deformed. Such deformations may leave measurable imprints on gravitational-wave signals and can be sourced through tidal interactions or the formation of mountains. We detail the formalism that describes fully-relativistic neutron star models with elastic crusts undergoing static perturbations. This… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 49 publications
3
56
0
Order By: Relevance
“…Focusing on the role of the matter model in our calculations, we found that the point where the strain was the largest for all the forces we considered was the top of the crust. This is where the crust yields which is consistent with previous calculations of neutron star crusts (Gittins et al 2020(Gittins et al , 2021. In Fig.…”
Section: A Solution To the Relativistic Laplace's Equationsupporting
confidence: 92%
See 1 more Smart Citation
“…Focusing on the role of the matter model in our calculations, we found that the point where the strain was the largest for all the forces we considered was the top of the crust. This is where the crust yields which is consistent with previous calculations of neutron star crusts (Gittins et al 2020(Gittins et al , 2021. In Fig.…”
Section: A Solution To the Relativistic Laplace's Equationsupporting
confidence: 92%
“…Since 0 needed to have a finite value at the base of the crust in the fluid star, we effectively violated the radial traction condition [cf. (A17) in Gittins et al (2020)]. However, we can still use the tangential traction condition to demand 2 ( base ) = 0.…”
Section: A Thermal Pressure Perturbation Outside the Corementioning
confidence: 99%
“…At the same time, more and louder detections offer the opportunity of going beyond a single radius measurement [140] or even a characterization of features of the equation of state such as phase transitions [123]. Improved detector sensitivity will allow us to measure higher order terms beyond the = 2 tidal deformability [74], directly observe the postmerger signal [38], and study the properties of the neutron star crust in terms of its elastic properties [334,335], heating [336], and shattering [337]. Another effect of interest is the potential resonant excitation of different neutron star modes driven by the orbital motion [338,339].…”
Section: Future Challenges and Opportunitiesmentioning
confidence: 99%
“…We assume that the onset of the crust elasticity is at 2 × 10 14 g cm −3 and that it finishes at 10 7 g cm −3 , where the liquid ocean/envelope is supposed to start (Pereira et al 2020). It is already known that such a shear modulus leads to negligible tidal deformation changes in ordinary NSs (Penner et al 2011;Gittins et al 2020), described in terms of zerofrequency non-radial perturbations. Therefore, one would expect that for other types of perturbations, they would also lead to negligible changes when compared to the perfect-fluid results.…”
Section: Shear Modulus For the Hadronic Phasementioning
confidence: 99%